Boron and nitrogen doped carbon loaded copper catalyst as well as preparation method and application thereof

By using boron and nitrogen doped carbon-supported copper catalyst (Cu@BNC), the problem of low C2H5OH activity and selectivity of Cu-based catalysts during CO2 reduction is solved, and the effect of high current density and high selectivity of C2H5OH is achieved.

CN119900044AActive Publication Date: 2025-04-29TIANJIN UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311401275.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

During the electrocatalytic CO2 reduction process of existing Cu-based catalysts, the reaction activity and selectivity of C2H5OH are low, and the current density is not sufficient to meet commercially feasible standards.

Method used

Boron and nitrogen doped carbon-supported copper catalyst (Cu@BNC) is prepared by impregnation and calcination methods to improve the dispersion and average valence state of Cu particles, enhance metal-carbon support interaction, and stabilize the oxygen-containing intermediates during the reaction.

Benefits of technology

In CO2RR, Cu@BNC catalysts exhibit high activity and selectivity, the Faraday efficiency (FE) of C2H5OH reaches 68%, and the partial current density reaches 179mA/cm2, which is better than the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900044A_ABST
    Figure CN119900044A_ABST
Patent Text Reader

Abstract

The invention discloses a boron and nitrogen-doped carbon-loaded copper catalyst and a preparation method and application thereof.The preparation method comprises the steps that excessive concentrated nitric acid is used for treating carbon, the treated carbon and copper nitrate are soaked at the room temperature, then an obtained precursor, a nitrogen source and a boron source are ground into powder at the room temperature, roasting is conducted at the specific temperature and time, and the boron and nitrogen-doped carbon-loaded copper catalyst is obtained. The boron and nitrogen doped carbon loaded copper catalyst is obtained. The catalyst disclosed by the invention can be applied to preparation of oxygen-containing products by electrocatalytic reduction of carbon dioxide. A stronger metal-carbon carrier interaction is induced mainly through B and N co-doped carbon, the average valence state of copper is improved, and a * CO-CO coupling way is promoted; as B has a relatively strong oxyphilic characteristic, an oxygen-containing intermediate in the reaction process is effectively stabilized, and breakage of a C-O bond is inhibited, so that high-activity and high-selectivity generation of an oxygen-containing product ethanol is promoted. And the catalyst shows excellent performance of preparing ethanol by reducing carbon dioxide in the process of preparing ethanol by reducing carbon dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic carbon dioxide reduction electrodes, and in particular, relates to a method for preparing a carbon-supported transition metal catalyst and its application in promoting the generation of oxygen-containing products. Background Art

[0002] Reducing dependence on fossil fuels and reducing the concentration of CO2 in the atmosphere are key issues of global concern. To achieve this goal, various measures have been taken to promote CO2 storage and conversion. Among them, the use of electrocatalytic CO2 reduction (CO2RR) to prepare high-value-added chemicals (CH3OH, HCOOH, C2H4 and C2H5OH, etc.) is a new method to convert renewable electrical energy into chemical energy and store it in fuels, which has received widespread attention. To promote the development of CO2RR technology, researchers have developed a series of metal and non-metal catalysts. Among the many metal catalysts, Cu has attracted widespread attention as the only metal catalyst that can produce C2+ products such as C2H4, C2H5OH and CH3COOH. However, to date, most Cu-based catalysts are more conducive to the production of C2H4 rather than liquid C2+ products. Although there are a few literature reports showing that the Faradaic efficiency (FE) of C2+ liquid products over oxide-derived Cu catalysts (OD-Cu) can reach 70% at extremely low overpotentials (>-0.3 V vs. RHE), the current density is often less than 10 mA / cm 2 (Zhou L, Lv R. Rational catalyst design and interface engineering for electrochemical CO2 reduction to high-valued alcohols [J]. Journal of Energy Chemistry, 2022, 70: 310-331). 2), the corresponding FE is often less than 40% (Gu J, Liu S, Ni W, et al. Modulating electric field distribution by alkali cations for CO2electroreduction in strongly acidic medium[J]. Nature Catalysis, 2022, 5(4): 268-276). Combined with literature analysis, the reasons for the low activity and selectivity of C2H5OH are mainly due to the following aspects: first, HER competition reaction; second, the high energy barrier of *CO-CO coupling makes the coupling process difficult; finally, in the actual reaction process, since the generation of C2H4 and C2H5OH shares the same reaction intermediate *OCCOH, the thermodynamic breakage of the CO bond is easier, which makes C2H4 easier to generate (LiM, Song N, Luo W, et al. Engineering surface oxophilicity of copper for electrochemical CO2 reduction to ethanol[J]. Advanced Science, 2023, 10(2): e2204579).

[0003] In order to improve the activity and selectivity of C2H5OH, researchers have proposed a variety of strategies, such as catalysts with specific grain boundaries or crystal planes, bimetallic catalysts, molecular catalysts, metal oxide-supported catalysts, etc. (Wang X, Wang Z, García de Arquer FP, et al. Efficient electrically powered CO2-to-ethanol via suppression of deoxygenation [J]. Nature Energy, 2020, 5 (6): 478-486). For example: Tang et al. constructed Ag-modified Cu2O materials, and increased the coverage of *CO on the catalyst surface by introducing CO-producing catalyst Ag to promote the *CO-CO coupling process. The prepared CuAg catalyst has a C2H5OH FE of 21.0% at -0.71V vs.RHE, and the partial current density of C2H5OH reaches 214.4mA / cm at -0.74V vs.RHE. 2, which is about twice that of the catalyst without Ag modification (Tang H, Liu Y, Zhou Y, et al. Boosting the electroreduction of CO2toethanol via the synergistic effect of Cu-Ag bimetallic catalysts [J]. ACS Applied Energy Materials, 2022, 5 (11): 14045-14052). Gao et al. designed a Cu-based electrocatalyst with abundant step sites, which selectively inhibited the formation of C2H4 by inhibiting the breakage of the CO bond of *CH2CHO, thereby promoting the production of alcohol products. Using this catalyst, 40.5% alcohol FE and 56.3 mA / cm 2 It is not difficult to find that although the corresponding research has made some progress, in most studies, the current density is still ≤100mA / cm -2 , the FE of C2H5OH is still below 60%. Therefore, it is still a challenge to develop Cu-based catalysts that can simultaneously achieve high current density and high selectivity for the production of C2H5OH. Summary of the invention

[0004] The present invention aims to solve the technical problems of low reaction activity and selectivity of Cu-based catalysts for preparing C2H5OH, and provides a copper catalyst supported by boron and nitrogen doped carbon (Cu@BNC) and a preparation method and application thereof. By means of impregnation and further calcination, B and N co-doped C (BNC) are used to induce stronger metal-carbon carrier interaction, so as to increase the average valence state of Cu and promote the *CO-CO coupling pathway, while improving the dispersibility of Cu; secondly, the strong oxygen affinity of B is used to stabilize the oxygen-containing intermediates in the reaction process and inhibit the breakage of the CO bond, so that it exhibits excellent reaction activity and selectivity in the preparation of C2H5OH by CO2 reduction, and can be used in the preparation of C2H5OH by CO2RR.

[0005] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:

[0006] A boron and nitrogen doped carbon-supported copper catalyst and a preparation method thereof, wherein Cu particles are uniformly supported on the catalyst surface, wherein the particle size of the Cu particles is 10-70 nm, preferably 10-36 nm, and the preparation is carried out according to the following steps:

[0007] Step 1: Treat the carbon powder with concentrated nitric acid to obtain carbon powder with surface defects.

[0008] In step 1, the toner is Ketjen Black (ECP-600JD) or Cabot VXC 72.

[0009] In step 1, the mass ratio of carbon powder to concentrated HNO3 solution is (0.5-1):100.

[0010] In step 1, carbon powder is added to a concentrated HNO3 solution with a mass percentage of 65-68wt%, and ultrasonically dispersed to obtain a suspension; the suspension is refluxed in an oil bath at a temperature of 80-100°C for 3-10 hours; after it is cooled to room temperature of 20-25°C, a solid sample is separated to obtain carbon powder with surface defects.

[0011] Step 2, uniformly dispersing the carbon powder obtained in step 1 into deionized water to obtain a carbon suspension, and adding a copper nitrate aqueous solution dropwise while continuing to disperse. After the addition is completed, continuing to fully disperse at room temperature of 20-25 degrees Celsius, and then collecting a solid sample; the amount of copper nitrate used is 100-150% of the mass of the carbon powder;

[0012] In step 2, mechanical stirring or ultrasound is used for dispersion, such as a stirring speed of 300-600 rpm, an ultrasound power of 500-1000w, and a time of 6-15 hours, preferably 10-12 hours.

[0013] In step 2, the dropping speed is 0.1-0.5 ml per minute.

[0014] Step 3, roasting the solid sample or the mixture thereof obtained in step 2, using the following scheme:

[0015] Solution 1: The solid sample obtained in step 2 is heated from room temperature 20-25 degrees Celsius to 200-300°C at a heating rate of 5-10 degrees Celsius per minute under a reducing atmosphere and kept heated for 1-2 hours, and then cooled naturally to room temperature;

[0016] Solution 2: The solid sample obtained in step 2 is mixed evenly with at least one of a nitrogen source and a boron source to obtain a mixture of solid samples, and heated to 800-900°C at a heating rate of 5-10°C per minute from room temperature of 20-25°C under an inert protective atmosphere and calcined for 1-2 hours, and then cooled naturally to room temperature.

[0017] In step 3, the nitrogen source is melamine or urea, and the boron source is boric acid; the mass ratio of the solid sample to the nitrogen source is 1:(5-10), and the mass ratio of the solid sample to the boron source is (5:2)-(10:1), preferably (5:2)-(4:1).

[0018] In step 3, the inert protective atmosphere is nitrogen, helium or argon.

[0019] In step 3, the reducing atmosphere is hydrogen.

[0020] Application of the catalyst of the present invention in preparing C2H5OH by CO2RR.

[0021] The catalyst of the present invention is sprayed onto a gas diffusion electrode (carbon paper) as a working electrode, a Hg / HgO electrode as a reference electrode, and IrO2 as a counter electrode, and assembled into an electrochemical cell; CO2 is introduced, the electrolyte is a 1 mol / L KOH aqueous solution, and electricity is applied to carry out an electrocatalytic reaction.

[0022] Furthermore, 0.5-1 mg of the catalyst of the present invention is sprayed per square centimeter of the gas diffusion electrode.

[0023] Compared with the prior art, the Cu@BNC catalyst of the present invention obtains a catalyst in which Cu particles are fully in contact with BNC. The introduction of the BNC carrier improves the dispersibility of the Cu particles, so that Cu particles with a particle size of 10-40nm are uniformly loaded on the BNC carrier. At the same time, the strong interaction between Cu and BNC increases the average valence state of Cu, promotes the *CO-CO coupling pathway, and thus improves the activity and selectivity of the CO2 reduction reaction.

[0024] The preparation method of Cu@BNC of the present invention uses commonly used conductive carbon black (Cabot VXC 72 or Ketjen Black) as a C source and copper nitrate as a copper source, and obtains the Cu@BNC catalyst by impregnation and further calcination. The raw materials required in the preparation process are simple, the preparation method is simple and easy, batch preparation can be realized, and it has certain industrialization prospects.

[0025] The Cu@BNC catalyst of the present invention is used for CO2RR to produce C2H5OH. The introduction of B and N co-doped C strengthens the electron transfer in the reaction process. At the same time, the strong interaction between Cu and BNC increases the average valence of Cu and promotes the *CO-CO coupling pathway. In addition, the introduction of B with strong oxygen affinity stabilizes the oxygen-containing intermediates in the reaction process and inhibits the breakage of the CO bond, so that the Cu@BNC catalyst exhibits good reaction activity and selectivity in CO2RR to produce C2H5OH. At -1.8V vs.RHE, the FE of C2H5OH reaches 68%, and the partial current density of C2H5OH reaches 179mA / cm 2 , and has excellent performance in CO2RR to C2H5OH. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The Raman spectra of C, BC, NC and BNC obtained in Examples 2, 4, 5 and 6 are shown.

[0027] Figure 2 The transmission electron microscope photograph and particle size statistics of Cu / C obtained in Example 7 are shown.

[0028] Figure 3 XRD diffraction spectra of Cu / C, Cu@BNC, Cu / BC and Cu@NC obtained in Examples 7, 12, 16 and 17.

[0029] Figure 4 The transmission electron microscope photo and particle size statistics of Cu / C obtained in Example 10 are shown.

[0030] Figure 5 TEM photos and particle size statistics of Cu@BNC obtained in Example 12.

[0031] Figure 6 TEM photograph and particle size statistics of Cu@BNC obtained in Example 15.

[0032] Figure 7 The transmission electron microscope photograph and particle size statistics of Cu / BC obtained in Example 16.

[0033] Figure 8 Transmission electron microscope photograph and particle size statistics of Cu@NC obtained in Example 17.

[0034] Fig. 9 The CO2 reduction performance test graph of C, BC, NC and BNC obtained in Examples 2, 4, 5 and 6 under the conditions of the examples.

[0035] Fig.10 The linear sweep voltammograms of Cu@BNC obtained in Examples 11-13 under the conditions of the examples are shown.

[0036] Fig.11 This is a test graph of the CO2 reduction performance of the Cu@BNC obtained in Examples 11-13 under the conditions of the examples.

[0037] Fig.12 The electrochemical impedance spectroscopy and contact angle test diagrams of Cu@BNC obtained in Examples 11-13.

[0038] Fig.13 Linear sweep voltammograms of Cu / C, Cu@BNC, Cu / BC and Cu@NC obtained in Examples 7, 12, 16 and 17 under the conditions of the examples.

[0039] Fig.14 This is a test graph of the CO2 reduction performance of Cu / C, Cu@BNC, Cu / BC and Cu@NC obtained in Examples 7, 12, 16 and 17 under the conditions of the examples.

[0040] Fig.15 Auger diagrams of Cu of Cu / C, Cu@BNC, Cu / BC and Cu@NC obtained in Examples 7, 12, 16 and 17.

[0041] Fig.16 N1s diagrams of Cu@BNC and Cu@NC obtained in Examples 12 and 17.

[0042] Fig.17 These are the in-situ infrared test images of Cu / C, Cu@BNC, Cu / BC and Cu@NC obtained in Examples 7, 12, 16 and 17. DETAILED DESCRIPTION

[0043] The present invention is further described in detail below through specific examples. The following examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way.

[0044] Example 1-C Preparation

[0045] 1 g of C (Ketjen Black) was accurately weighed and dispersed in 200 mL of commercially available concentrated HNO3 solution (mass percentage of 65-68 wt%), and ultrasonically treated for 1 h. Then, it was refluxed in an oil bath at 80°C for 3 h. After cooling to room temperature, the solid sample was collected by centrifugation and washed with ultrapure water until the supernatant was neutral. The obtained black solid sample was dried at 60°C to obtain C with rich surface defects.

[0046] Example 2—Preparation of C

[0047] 1 g of C (Ketjen Black) was accurately weighed and dispersed in 100 mL of a commercially available concentrated HNO3 solution (mass percentage of 65-68 wt%), and then ultrasonically treated for 1 h. Then, it was refluxed in an oil bath at 100°C for 9 h. After cooling to room temperature, the solid sample was collected by centrifugation and washed with ultrapure water until the supernatant was neutral. The obtained black solid sample was dried at 60°C to obtain C with surface defects. Figure 1 The Raman spectrum of C prepared in Example 2 is included, from which it can be seen that the ratio of the D band to the G band of C (I D :I G ) is 1.14.

[0048] Example 3—Preparation of C

[0049] The difference from Example 2 is that Cabot VXC 72 is used instead of Ketjen Black (ECP-600JD).

[0050] Example 4—Preparation of BC

[0051] 0.1 g of C obtained in Example 2 was mixed with boric acid in a mass ratio of 4:1, and then in an oxygen-excluded tube furnace, an inert protective atmosphere was continuously provided at 80 standard cubic centimeters (sccm) of N2 per minute, and the temperature was heated from room temperature 20-25 degrees Celsius at a rate of 5 degrees Celsius per minute to 800°C and maintained for 1 hour to obtain the final BC. Figure 1 The Raman spectrum of BC prepared in Example 4 is included; it can be seen that the I D :I G is 1.20.

[0052] Example 5—Preparation of NC

[0053] 0.1 g of C obtained in Example 2 was mixed with melamine in a mass ratio of 1:5, and then in an oxygen-excluded tube furnace, an inert protective atmosphere was continuously provided at 80 standard cubic centimeters (sccm) of N2 per minute, and the mixture was heated from room temperature (20-25 degrees Celsius) to 800°C at a heating rate of 5 degrees Celsius per minute and maintained for 1 hour to obtain the final NC. Figure 1 The Raman spectrum of NC prepared in Example 5 is included; it can be seen that the I D :I G is 1.25.

[0054] Example 6—Preparation of BNCs

[0055] 0.1 g of C obtained in Example 2 was mixed with melamine in a mass ratio of 1:5, and then boric acid was added and mixed evenly, wherein the mass ratio of C to boric acid in Example 2 was 4:1, and then in a tubular furnace excluding oxygen, an inert protective atmosphere was continuously provided at 80 standard cubic centimeters (sccm) of N2 per minute, and the temperature was heated from room temperature of 20-25 degrees Celsius to 800°C at a heating rate of 5 degrees Celsius per minute and maintained for 1 hour to obtain the final BNC. Figure 1 The Raman spectrum of BNC prepared in Example 6 is included; it can be seen that the I D :I G It is 1.29.

[0056] Example 7—Preparation of Cu / C

[0057] (1) 0.1 g of C obtained in Example 2 was added to 30 mL of deionized water and subjected to ultrasonic treatment for 1 h to obtain a C suspension; then 10 mL of a copper nitrate aqueous solution (15 mg / mL) was added dropwise to the C suspension under vigorous stirring (stirring speed was 300-600 rpm), stirred for 12 h, and then the product was collected by centrifugation and dried at 60°C.

[0058] (2) The obtained powder is placed in a tubular furnace with oxygen excluded and a reducing atmosphere maintained with a 30 sccm H2 gas flow, and is heated from room temperature (20-25 degrees Celsius) to 200°C at a heating rate of 10 degrees Celsius per minute and maintained for 1 hour. After it is naturally cooled to room temperature, Cu / C is obtained.

[0059] Figure 2 Figure a is a transmission electron microscope photo of Cu / C prepared in Example 7, from which it can be seen that the Cu particles are uniformly loaded on the surface of C. Figure b is the particle size distribution of Cu / C prepared in Example 7, from which it can be seen that the particle size distribution of Cu is 14-24 nm. Figure 3 The XRD spectrum of Cu / C prepared in Example 7 is shown in Figure 1. It can be seen that, except for the diffraction peak at about 20° (2Theta) belonging to C, the remaining diffraction peaks completely match the standard card of Cu (PDF#04-0836), indicating that Cu with good crystallinity is obtained.

[0060] Example 8—Preparation of Cu / C

[0061] The difference from Example 7 is that C obtained in Example 1 is used to replace C obtained in Example 2.

[0062] Example 9—Preparation of Cu / C

[0063] The difference from Example 7 is that the concentration of the copper nitrate aqueous solution used is 10 mg / mL.

[0064] Example 10—Preparation of Cu / C

[0065] The difference from Example 7 is that the carbon obtained in Example 3 is used to replace the carbon obtained in Example 2. Figure 4 Figure a is a transmission electron microscope photo of the Cu / C prepared in Example 10, from which it can be seen that the Cu particles are uniformly loaded on the surface of C. Figure b is the particle size distribution of the Cu / C prepared in Example 10, from which it can be seen that the particle size distribution of Cu is 20-70 nm.

[0066] Example 11—Preparation of Cu@BNC

[0067] (1) 0.1 g of C obtained in Example 2 was added to 30 mL of deionized water and subjected to ultrasonic treatment for 1 h to obtain a C suspension; then 10 mL of a copper nitrate aqueous solution (15 mg / mL) was added dropwise to the C suspension under vigorous stirring (stirring speed was 300-600 rpm), stirred for 12 h, and then the product was collected by centrifugation and dried at 60°C.

[0068] (2) The solid powder obtained in step (1) is uniformly mixed with melamine and boric acid, wherein the mass ratio of the solid powder obtained in step (1) to melamine is 1:5, and the mass ratio of the solid powder obtained in step (1) to boric acid is 10:1; and then, in a tubular furnace excluding oxygen, an inert protective atmosphere is continuously provided at 50 standard cubic centimeters (sccm) of N2 per minute, and the mixture is heated from room temperature of 20-25 degrees Celsius to 800°C at a heating rate of 5 degrees Celsius per minute and maintained for 1 hour, and then naturally cooled to room temperature to obtain Cu@BNC.

[0069] Example 12—Preparation of Cu@BNC

[0070] The difference from Example 11 is that in step (2), the solid powder is mixed with melamine in a mass ratio of 1:5 and with boric acid in a mass ratio of 4:1.

[0071] Figure 5 Figure a is the transmission electron micrograph of the Cu@BNC prepared in Example 12, from which it can be seen that the Cu particles are uniformly loaded on the C surface; Figure b is the particle size distribution of the Cu@BNC prepared in Example 12, from which it can be seen that the particle size distribution of Cu is between 10 and 20 nm. Figure 3 The XRD spectrum of Cu@BNC prepared in Example 12 is shown in the figure. It can be seen that except for the diffraction peak at about 20° (2Theta) belonging to C, the other diffraction peaks completely match the standard card of Cu (PDF#04-0836), indicating that Cu with good crystallinity is obtained.

[0072] Example 13—Preparation of Cu@BNC

[0073] The difference from Example 11 is that in step (2), the solid powder is mixed with melamine in a mass ratio of 1:5 and with boric acid in a mass ratio of 5:2.

[0074] Example 14—Preparation of Cu@BNC

[0075] The difference from Example 12 is that in step (2), urea is used instead of melamine and the mass ratio of solid powder to urea is 1:10.

[0076] Example 15—Preparation of Cu@BNC

[0077] The difference from Example 12 is that in step (3), the calcination temperature is 900° C. and the time is 2 h.

[0078] Figure 6 Figure a is a transmission electron microscope image of the Cu@BNC prepared in Example 15, from which it can be seen that the Cu particles are uniformly loaded on the surface of C. Figure b is a particle size distribution image of the Cu@BNC prepared in Example 15, from which it can be seen that the particle size distribution of Cu is 14-24 nm.

[0079] Example 16—Preparation of Cu / BC

[0080] The difference from Example 12 is that in step (2), melamine is not added.

[0081] Figure 7 Figure a is the transmission electron micrograph of the Cu / BC prepared in Example 16, from which it can be seen that the Cu particles are uniformly loaded on the C surface; figure b is the particle size distribution of the Cu / BC prepared in Example 16, from which it can be seen that the particle size distribution of Cu is between 22 and 36 nm. Figure 3 The XRD spectrum of Cu / BC prepared in Example 16 is shown in Figure 14. It can be seen that, except for the diffraction peak at about 20° (2Theta) belonging to C, the remaining diffraction peaks completely match the standard card of Cu (PDF#04-0836), indicating that Cu with good crystallinity is obtained.

[0082] Example 17—Preparation of Cu / NC

[0083] The difference from Example 12 is that in step (2), no boric acid is added.

[0084] Figure 8 Figure a is the transmission electron micrograph of the Cu / BC prepared in Example 17, from which it can be seen that the Cu particles are uniformly loaded on the C surface; figure b is the particle size distribution of the Cu / BC prepared in Example 17, from which it can be seen that the particle size distribution of Cu is between 22 and 36 nm. Figure 3The XRD spectrum of Cu / BC prepared in Example 17 is shown in Figure 17. It can be seen that, except for the diffraction peak at about 20° (2Theta) belonging to C, the remaining diffraction peaks completely match the standard card of Cu (PDF#04-0836), indicating that Cu with good crystallinity is obtained.

[0085] Embodiment 18

[0086] The catalysts prepared in Examples 1-17 were tested for their electrocatalytic CO2 reduction performance.

[0087] The catalyst prepared in Examples 1-17 was sprayed onto carbon paper as a working electrode (0.5-1 mg of catalyst was sprayed per square centimeter of electrode), Hg / HgO was used as a reference electrode, and IrO2 supported on a Ti mesh was used as a counter electrode. The cells were assembled into a flow electrochemical cell. CO2 was continuously introduced into the electrochemical cell to perform an electrocatalytic CO2 reduction performance test and an electrode stability test. The electrolyte was a 1 mol / L KOH aqueous solution, and the working electrode area was 1 cm 2 The gas phase products were detected by gas chromatography, and the liquid phase products were detected by a quantitative method combining liquid chromatography and nuclear magnetic resonance.

[0088] The product distribution of 0.5 mg of the catalyst prepared in Examples 1-3 at an applied potential of -1.8 V vs. RHE is shown in the following table.

[0089] CO FE (%) <![CDATA[H2 FE(%)]]> Example 1 1.9 98.1 Example 2 2.3 97.7 Example 3 1.8 98.2

[0090] The product distribution of 1 mg of catalyst prepared in Examples 2, 4, 5 and 6 at -0.8 to -2 V vs. RHE is as follows: Fig. 9 As shown. Wherein a is the CO2 reduction performance of C prepared in Example 2. The experimental results show that the product of C catalyst is mainly H2, and a small amount of CO. b is the CO2 reduction performance of BC prepared in Example 4. The experimental results show that the product of BC catalyst is mainly H2, and a small amount of CO and HCOOH. c is the CO2 reduction performance of NC prepared in Example 5. The experimental results show that the products of NC catalyst are mainly H2 and CO. d is the CO2 reduction performance of BNC prepared in Example 6. The experimental results show that the products of BNC catalyst are mainly H2, CO and HCOOH.

[0091] From the above results, it can be found that compared with undoped C, the introduction of B induced the generation of more CO and HCOOH; the introduction of N element inhibited the generation of H2 and effectively promoted the generation of CO; on BNC, the generation of H2 was further inhibited and the selectivity of carbon-containing products was further improved.

[0092] The FE of C2H5OH of 0.5 mg of the catalyst prepared in Examples 7-10 at -1.8 V vs. RHE is shown in the following table.

[0093] <![CDATA[C2H5OH FE(%)]]> Example 7 22.9 Example 8 23.7 Example 9 23.1 Example 10 16.1

[0094] From the above content, it can be seen that compared with Example 7 and Example 9, within the given range, the change in the amount of copper nitrate added has basically no effect on the FE of C2H5OH. However, when Cabot VXC 72 is used to replace Ketjen Black, it can be found that the FE of C2H5OH has decreased significantly. Figure 4 It can be seen that the main reason for the decrease in FE of C2H5OH is the significant increase in the particle size of Cu.

[0095] The reaction activity and product distribution of 0.5 mg of the catalyst prepared in Examples 11-13 at -0.8 to -2 V vs. RHE are shown in Figure 2. Fig.10 and 11 shown.

[0096] Fig.10 The linear sweep voltammetry (LSV) curves of Examples 11-13 are shown in FIG. Fig.11 In the figure, a is the CO2 reduction performance result of Cu@BNC prepared in Example 11, indicating that the FE of C2H5OH is 52.4% at -1.8V vs.RHE; b is the CO2 reduction performance result of Cu@BNC prepared in Example 12, indicating that the FE of C2H5OH is 68.1% at -1.8V vs.RHE; c is the CO2 reduction performance result of Cu@BNC prepared in Example 13, indicating that the FE of C2H5OH is 28.4% at -1.8V vs.RHE.

[0097] It can be seen that with the increase of the amount of B added, the CO2RR activity shows a trend of first increasing and then decreasing, and the FE of C2H5OH also shows a similar trend. Analyzing the reasons for this phenomenon, on the one hand, a small amount of B doping can significantly reduce the electron transfer impedance, while when the amount of B is too much, it will have an adverse effect on the electron conduction in the reaction process (such as Fig.12 On the other hand, excessive B doping will significantly reduce the hydrophobicity of the material surface. The reduction in hydrophobicity will cause the electrode surface to be covered by the aqueous solution, resulting in * H intermediates accumulate on the catalyst surface, promoting HER side reactions (such as Fig.12 (as shown in b).

[0098] The FE of C2H5OH at -1.8 V vs. RHE for 1 mg of the catalysts prepared in Examples 12, 14 and 15 is shown in the following table.

[0099] <![CDATA[C2H5OH FE(%)]]> Example 12 68.0 Embodiment 14 67.1 Embodiment 15 60.7

[0100] Combination Fig.11 As can be seen from the table above, changing the catalyst loading and the type of nitrogen source has little effect on the FE of C2H5OH. As can be seen from the table, as the calcination temperature increases, the FE of C2H5OH decreases slightly. The reaction activity and product distribution of 1 mg of catalyst prepared in Examples 7, 12, 16 and 17 at -0.8 to -2 V vs. RHE are shown in Figure 2. Fig.13 and Fig.14 shown.

[0101] Fig.13 ] are the LSV curves of Examples 7, 12, 16 and 17. Fig.14 In the figure, a is the CO2RR performance result of Cu / C prepared in Example 7, indicating that the FE of C2H5OH is 23.7% at -1.8 V vs. RHE; b is the CO2RR performance result of Cu@BNC prepared in Example 12, indicating that the FE of C2H5OH is 68.0% at -1.8 V vs. RHE; c is the CO2RR performance result of Cu / BC prepared in Example 16, indicating that the FE of C2H5OH is 29.4% at -1.8 V vs. RHE; d is the CO2RR performance result of Cu@NC prepared in Example 17, indicating that the FE of C2H5OH is 34.0% at -1.8 V vs. RHE.

[0102] From the LSV curve, it can be seen that the CO2RR activity of the obtained catalysts follows the order of Cu@BNC>Cu@NC>Cu / BC>Cu / C. From the product distribution, it can be seen that the CO2RR products of Cu / C are mainly gas phase products CO and C2H4 and liquid phase product C2H5OH ( Fig.14 As shown in a). With the introduction of element B, the FE of H2 decreased slightly, the distribution of CO2RR products changed, the FE of CO and C2H4 decreased significantly, and the liquid products HCOOH and C2H5OH increased ( Fig.14 For Cu@NC, the doping of N element significantly inhibits the HER reaction and significantly improves the FE of CO2RR products, but the product distribution is relatively uniform and the FE of a single product is relatively low ( Fig.14 For Cu@BNC, the generation of H2 was further suppressed, and at the same time, the product distribution also changed significantly: the generation of CO and C2H4 was significantly suppressed, and the FE of the products HCOOH and C2H5OH was significantly improved ( Fig.14By comparing the above results, it can be found that the doping of N element can effectively inhibit the HER reaction, while the introduction of B element is more conducive to the generation of liquid phase products HCOOH and C2H5OH.

[0103] From the Auger diagram of Cu, it can be seen that with the introduction of B, N, and B and N, the valence state of Cu gradually changes from Cu 0 Convert to Cu + ( Fig.15 ). The main reason for this phenomenon is that the doping of B and N induces the metal-support interaction, which causes the charge redistribution at the interface site between Cu and B and N doped C support, thus affecting the valence state of Cu. In addition, a higher proportion of Cu + This means a stronger electronic metal-carbon carrier interaction. Compared with single element doping, B and N co-doping obviously has a higher proportion of Cu + , that is, the order of metal-support interaction strength of the four catalysts we prepared is Cu@BNC>Cu@NC>Cu / BC>Cu / C. It can be found that the order of CO2RR activity is consistent with the strength of metal-C support interaction. In addition, from the peak separation results of N1s, it can be seen that compared with simple N doping, the introduction of B induces the formation of more basic pyridinic N species ( Fig.16 ), can effectively enhance the adsorption of CO2. Fig.17 As shown, the in-situ infrared test images of Examples 7, 12, 16 and 17, 2100cm -1 The peak at 1650cm is the CO stretching vibration of *CO. -1 The signal at 1610 cm -1An obvious signal is also observed around, and this peak can be attributed to the intermediate *OCCOH after *CO-CO coupling. Compared with the catalysts obtained in Examples 7, 16 and 17, *CO can be observed in a wider voltage range on the catalyst obtained in Example 12, indicating that *CO is more stable on the catalyst obtained in Example 12. Combining the experimental and characterization results, it can be analyzed that the main reasons for promoting the generation of C2H5OH come from the following aspects. First, in the catalyst obtained in Example 12, there are more pyridine N species, which strengthens the adsorption of CO2, increases the local CO2 concentration, and is more conducive to subsequent conversion; on the other hand, the catalyst obtained in Example 12 has a stronger metal-C carrier interaction, which induces the formation of more positive Cu species, which is conducive to the adsorption and stabilization of *CO, and thus is more conducive to the subsequent *CO-CO coupling process. In addition, since B has a relatively strong oxygen-philic property, it can effectively stabilize the oxygen-containing intermediates in the reaction process and inhibit the breakage of the CO bond, and is more conducive to the generation of oxygen-containing products.

[0104] In summary, the boron and / or nitrogen-doped carbon-supported copper catalyst of the present invention exhibits good activity and selectivity for the electrocatalytic reduction of CO2 to C2H5OH. At -1.8 V vs. RHE, the FE of C2H5OH reached 68%, and the partial current density of C2H5OH reached 179 mA / cm 2 The results of in situ ATR-SEIRAS and electrochemical experiments show that the co-doping of B and N induces a stronger metal-support interaction, increases the average valence state of Cu and promotes the *CO-CO coupling pathway; the introduction of B induces the formation of more pyridinic N species, enhances the adsorption of CO2, and enriches the local concentration of the reactants; in addition, due to the relatively strong oxygen-philic properties of B, it can effectively stabilize the oxygen-containing intermediates in the reaction process and inhibit the breakage of the CO bond, thereby promoting the highly active and highly selective generation of the oxygen-containing product C2H5OH.

[0105] According to the content of the present invention, the process parameters can be adjusted to achieve the preparation of the catalyst of the present invention, and the performance substantially consistent with the present invention is shown after testing. The present invention is described exemplarily above, and it should be noted that any simple deformation, modification or equivalent replacement that can be made by other technicians in this field without spending creative labor falls within the protection scope of the present invention without departing from the core of the present invention.

Claims

1. A boron and nitrogen doped carbon supported copper catalyst, characterized in that: The Cu particles are uniformly loaded on the catalyst surface, wherein the particle size of the Cu particles is 10-70 nm, and the preparation is carried out according to the following steps: Step 1, using concentrated nitric acid to treat carbon powder to obtain carbon powder with surface defects, the mass ratio of carbon powder to concentrated HNO3 solution is (0.5-1):100; Step 2, uniformly dispersing the carbon powder obtained in step 1 into deionized water to obtain a carbon suspension, and adding a copper nitrate aqueous solution dropwise while continuing to disperse. After the addition is completed, continuing to fully disperse at room temperature of 20-25 degrees Celsius, and then collecting a solid sample; the amount of copper nitrate used is 100-150% of the mass of the carbon powder; Step 3, roasting the solid sample or the mixture thereof obtained in step 2, using the following scheme: Solution 1: The solid sample obtained in step 2 is heated from room temperature 20-25 degrees Celsius to 200-300°C at a heating rate of 5-10 degrees Celsius per minute under a reducing atmosphere and kept heated for 1-2 hours, and then cooled naturally to room temperature; Solution 2, the solid sample obtained in step 2 is evenly mixed with at least one of a nitrogen source substance and a boron source substance to obtain a mixture of solid samples, and heated from room temperature of 20-25 degrees Celsius to 800-900°C at a heating rate of 5-10 degrees Celsius per minute under an inert protective atmosphere and kept for roasting for 1-2 hours, and then naturally cooled to room temperature; the nitrogen source substance is melamine or urea, and the boron source substance is boric acid; the mass ratio of the solid sample to the nitrogen source substance is 1:(5-10), and the mass ratio of the solid sample to the boron source substance is (5:2)-(10:1).

2. The boron and nitrogen doped carbon supported copper catalyst according to claim 1, characterized in that: The particle size of Cu particles is 10-36nm.

3. The boron and nitrogen doped carbon supported copper catalyst according to claim 1, characterized in that: In step 1, the carbon powder is Ketjen black (ECP-600JD) or Cabot VXC 72; the carbon powder is added to a concentrated HNO3 solution at a mass percentage of 65-68wt%, and ultrasonically dispersed to obtain a suspension; the suspension is refluxed in an oil bath at a temperature of 80-100°C for 3-10 hours; After cooling to room temperature (20-25 degrees Celsius), the solid sample is separated to obtain carbon powder with surface defects.

4. The boron and nitrogen doped carbon supported copper catalyst according to claim 1, characterized in that: In step 2, mechanical stirring or ultrasound is used for dispersion, such as a stirring speed of 300-600 rpm, an ultrasound power of 500-1000w, a time of 6-15 hours, preferably 10-12 hours; and a dropping speed of 0.1-0.5 ml per minute.

5. The boron and nitrogen doped carbon supported copper catalyst according to claim 1, characterized in that: In step 3, the inert protective atmosphere is nitrogen, helium or argon; the reducing atmosphere is hydrogen; and the mass ratio of the solid sample to the boron source material is (5:2)-(4:1).

6. A method for preparing a boron and nitrogen doped carbon supported copper catalyst, characterized in that: Prepare according to the following steps: Step 1, using concentrated nitric acid to treat carbon powder to obtain carbon powder with surface defects, the mass ratio of carbon powder to concentrated HNO3 solution is (0.5-1):100; Step 2, uniformly dispersing the carbon powder obtained in step 1 into deionized water to obtain a carbon suspension, and adding a copper nitrate aqueous solution dropwise while continuing to disperse. After the addition is completed, continuing to fully disperse at room temperature of 20-25 degrees Celsius, and then collecting a solid sample; the amount of copper nitrate used is 100-150% of the mass of the carbon powder; Step 3, roasting the solid sample or the mixture thereof obtained in step 2, using the following scheme: Solution 1: The solid sample obtained in step 2 is heated from room temperature 20-25 degrees Celsius to 200-300°C at a heating rate of 5-10 degrees Celsius per minute under a reducing atmosphere and kept heated for 1-2 hours, and then cooled naturally to room temperature; Solution 2, the solid sample obtained in step 2 is evenly mixed with at least one of a nitrogen source substance and a boron source substance to obtain a mixture of solid samples, and heated from room temperature of 20-25 degrees Celsius to 800-900°C at a heating rate of 5-10 degrees Celsius per minute under an inert protective atmosphere and kept for roasting for 1-2 hours, and then naturally cooled to room temperature; the nitrogen source substance is melamine or urea, and the boron source substance is boric acid; the mass ratio of the solid sample to the nitrogen source substance is 1:(5-10), and the mass ratio of the solid sample to the boron source substance is (5:2)-(10:1).

7. The method for preparing a boron and nitrogen doped carbon supported copper catalyst according to claim 6, characterized in that: In step 1, the carbon powder is Ketjen black or Cabot VXC 72; the carbon powder is added to a concentrated HNO3 solution at a mass percentage of 65-68wt%, and ultrasonically dispersed to obtain a suspension; the suspension is refluxed in an oil bath at a temperature of 80-100°C for 3-10 hours; After cooling to room temperature of 20-25 degrees Celsius, separate the solid sample to obtain carbon powder with surface defects; in step 2, use mechanical stirring or ultrasound for dispersion, such as a stirring speed of 300-600 rpm, an ultrasonic power of 500-1000w, and a time of 6-15 hours, preferably 10-12 hours; the dropping speed is 0.1-0.5ml per minute; in step 3, the inert protective atmosphere is nitrogen, helium or argon; the reducing atmosphere is hydrogen; the mass ratio of the solid sample to the boron source material is (5:2)-(4:1).

8. Use of a boron and nitrogen doped carbon supported copper catalyst as claimed in any one of claims 1 to 5 in the preparation of C2H5OH by CO2RR.

9. The use according to claim 8, characterized in that: Boron and nitrogen doped carbon-loaded copper catalysts are sprayed onto a gas diffusion electrode (such as carbon paper) as a working electrode, a Hg / HgO electrode as a reference electrode, and IrO2 as a counter electrode, and assembled into an electrochemical cell; CO2 is introduced, the electrolyte is a 1 mol / L KOH aqueous solution, and electricity is applied for an electrocatalytic reaction.

10. The use according to claim 8, characterized in that: 0.5-1 mg of boron- and nitrogen-doped carbon-supported copper catalyst was sprayed per square centimeter of gas diffusion electrode.

Citation Information

Patent Citations

  • Preparation method for nitrogen-boron-doped carbon-based catalyst

    CN104998675A

  • Boron and nitrogen doped carbon porous nanosheet loaded transition metal nanoparticle material catalyst and preparation method and application thereof

    CN110639592A

  • Nitrogen-doped cuprous oxide electrocatalyst, preparation method, electrode and application

    CN113249748A

  • Bimetal-loaded boron-doped carbon nitride nanosheet heterojunction as well as preparation method and application thereof

    CN113731470A

  • Preparation method and application of boron-nitrogen co-coordinated copper monatomic catalyst

    CN114807991A